Retracted: Fast Recognition Method of Football Robot’s Graphics From the VR Perspective - Zhen Bai; Liang Wang; Sheng Zhou; Yuan Cao; Ying Liu; Jie Zhang (IEEE Access)
The purpose of this article is to identify football and related environmental variables through its VR images under the current situation where the vision system has become the only way for football robots to obtain the external environment, so as to improve the chances of winning the game. First, this article uses color filters to enhance the VR football data to distinguish between shadow games and aliens. The best environment for enhancing the image is automatically determined by the Ostu method, so that the image is not affected by shadows as much as possible, and the outline of the image can be sealed. At the same time, using the humanoid medium-sized football game machine system as the platform, the relevant processing algorithms of the humanoid football robot front-view system are studied to realize the work of color image segmentation, edge extraction, straight line extraction, cross-line recognition and target post-recognition. PA-SIFT algorithm is used to quickly identify the graphics. Data verification results show that the recognition rate of the PA-SIFT algorithm can reach 96%, ensuring the real-time and feasibility of the algorithm. In addition, the divide-and-conquer algorithm and the related processing algorithm of the vision system are combined to determine the central area of the image, so that the algorithm is not affected by the external environment, and the algorithm is robust and can improve actual competition.